Impact of new electrocardiographic criteria in arrhythmogenic cardiomyopathy - Hauer, Richard N.; Cox, Moniek; Groeneweg, Judith (Frontiers in Physiology, 2012)
Arrhythmogenic cardiomyopathy (AC) has originally been described as a disorder characterized by fibrofatty replacement of the myocardium, primarily of the right ventricle (RV), and ventricular tachyarrhythmias, sudden death, and at a late stage progressive heart failure. Arrhythmogenic right ventricular dysplasia or cardiomyopathy (ARVD/C) was the previous name of the disease. However, similar histopathologic changes are also found in the left ventricle (LV). AC is also considered a hereditary disease. Recent molecular genetic studies provide accumulating evidence that fibrofatty replacement is preceded by mutation-related desmosomal changes. Desmosomal dysfunction may lead to mechanical and thereafter electrical uncoupling, ultimately resulting in conduction delay. This activation delay and conduction block, provide a substrate for re-entrant mechanisms and thereby ventricular tachycardia (VT). The gold standard for AC diagnosis is demonstration of transmural fibrofatty replacement in cardiac tissue obtained by autopsy or surgery. To facilitate diagnosis in clinical practice, an international Task Force defined in 1994 a set of criteria (TFC) based on electrocardiographic, functional and morphologic features, and family history. These criteria have recently been revised. Routine 12-lead electrocardiography is one of the most important tools for AC diagnosis in all stages of the disease. Even in the absence of other markers in the early concealed stage of the disease, in line with early slow conduction and electrical uncoupling ECG analysis may contribute to early diagnosis. Activation delay and site of origin of VT are reflected in various characteristics of the surface 12-lead electrocardiogram. Since the ECG is easy to obtain, this technique is particularly useful, for both diagnosis and follow up of disease progression.